2012
DOI: 10.3390/w4010063
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impacts on Water Availability and Use in the Limpopo River Basin

Abstract: This paper analyzes the effects of climate change on water availability and use in the Limpopo River Basin of Southern Africa, using a linked modeling system consisting of a semi-distributed global hydrological model and the Water Simulation Module (WSM) of the International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT). Although the WSM simulates all major water use sectors, the focus of this study is to evaluate the implications of climate change on irrigation water supply in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 20 publications
2
37
1
Order By: Relevance
“…Southern African water resources are regarded as being highly affected by seasonal variability, a fact that is likely to be exacerbated by climate change (Kusangaya et al, 2014). Zhu and Ringler (2010) estimated a decrease in Limpopo streamflow by 2030 due to climate change, which is contradictory to studies that found increases of precipitation (Tadross et al, 2005) and runoff (Li et al, 2015) in parts of southern Africa, including vast parts of the Limpopo Basin.…”
Section: Introductioncontrasting
confidence: 38%
“…Southern African water resources are regarded as being highly affected by seasonal variability, a fact that is likely to be exacerbated by climate change (Kusangaya et al, 2014). Zhu and Ringler (2010) estimated a decrease in Limpopo streamflow by 2030 due to climate change, which is contradictory to studies that found increases of precipitation (Tadross et al, 2005) and runoff (Li et al, 2015) in parts of southern Africa, including vast parts of the Limpopo Basin.…”
Section: Introductioncontrasting
confidence: 38%
“…The Limpopo River basin is expected to face even more serious water scarcity issues in the future, limiting economic development in the basin (Zhu and Ringler, 2012). To apply this framework at the regional scale, a finer-resolution version of the global hydrological model PCRaster Global Water Balance (PCR-GLOBWB) was adapted to regional conditions in the basin.…”
Section: P Trambauer Et Al: Identification and Simulation Of Past Hmentioning
confidence: 99%
“…It will lead to decreasing precipitation rates and increase drought events [4]. Thus, water management and infrastructure changes have been expected to improve the situation if current climate conditions continue into the future [5]. On a global view, 70 % of the freshwater resources are used for agricultural purposes, and only 19 % for industrial and 11 % for domestic purposes (including drinking, washing, food preparation and sanitation) [6].…”
Section: Introductionmentioning
confidence: 99%